Isolated from Populus euphratica rhizosphere soil, and mining their metabolites - Zhang, Jia-xin; Chen, Yi-huang; Luo, Xinrong; Zhang, Li-li; Luo, Xiao-xia (Frontiers in Microbiology, 2025)
IntroductionThe microbial community in desert ecosystems is a vital and highly active component. Streptomyces, one of the dominant genera within this community, exhibits significant capabilities in metabolic degradation and the synthesis of secondary metabolites.MethodsTo investigate the metabolic potential of Streptomyces desertis, two strains of Streptomyces were isolated from rhizosphere soil samples of Populus euphratica in the Taklimakan Desert during the initial phase of this study, TRM 70351T and TRM 70361T.ResultsThe identification of these strains as belonging to the genus Streptomyces was confirmed through 16S rRNA sequencing. All calculated Average Nucleotide Identity (ANI) values were below the 95% cut-off recommended for distinguishing distinct species, and the estimated digital DNA-DNA hybridization (dDDH) values were all below the suggested threshold of 70% for species delineation. Results from phylogenetic, genomic, phenotypic, and chemotaxonomic analyses confirmed that TRM 70351T and TRM 70361T represent two new species within the genus Streptomyces, designated as Streptomyces solitudinis sp. nov. and Streptomyces rubellus sp. nov. The type strain for Streptomyces solitudinis sp. nov. is TRM 70351T ( = CCTCC AA 2020049T = LMG 32404T), while the type strain for Streptomyces rubellus sp. nov. is TRM 70361T ( = CCTCC AA 2020043T = JCM 35793T). Notably, Among the identified gene clusters of TRM 70351T, cluster 12.1 was predicted to be the biosynthetic gene cluster responsible for producing the aminoglycoside compound streptomycin, exhibiting a similarity of 55%. In this study, HSQC-TOCSY was employed to detect the presence of aminoglycosides in fermentation medium No. 1, while LC-MS/MS was utilized to analyze the molecular fragments of neomycin and streptomycin in the alkaline aqueous phase sample of the fermentation product. The mixture was eluted using methanol and ammonia water in a 3:1 ratio, leading to the further separation of the compounds daidzein and Tridec-1-ene.DiscussionThis study has enhanced the species resources of Streptomyces deserticum and the diversity of aminoglycoside compound-producing bacteria. TRM 70351T exhibited unique metabolic potential, indicating that further studies could be conducted in the future.